Complications of Varicella in Unvaccinated Children From Romania, 2002–2013: A Retrospective Study. Issue 2 (February 2016) - Popescu, Corneliu Petru; Ceausu, Emanoil; Florescu, Simin Aysel; Chirita, Daniel; Ruta, Simona
Abstract : The epidemiologic and clinical pattern of varicella-related hospitalizations recorded during 2002–2013 in Romania showed the highest hospitalization rate in the 0–1 year age group. Younger age and diagnosis after 2007 were independent predictors of varicella-related complications, recorded in half of the hospitalized cases. Abstract : Supplemental Digital Content is available in the text.